GAZE TRACKING SYSTEMS FOR HUMAN-COMPUTER INTERFACE (Perner's Contacts, 2011)
This article deals with currently used gaze tracking systems, their classification and application possibilities. Further are presented selected gaze tracking systems suitable for human-computer interface. Finally are proposed improvements of these systems based on analysis of their weak and strength points.
Keywords: Gaze tracking; Human-computer interface; image processing